Advancing Single Cell Transcriptomic Analysis through Self Supervised Deep Learning Architectures for Cellular Heterogeneity Discovery - Peter Prescott; Henry Whitman; Gric Blackwood (Bioinformatics Insights and Analytics, 2026)
The emergence of single-cell RNA sequencing has fundamentally transformed modern biological sciences by enabling the characterization of cellular states at an unprecedented transcriptomic resolution. However, traditional computational workflows remain constrained by data sparsity, massive technical noise, dropout events, and extreme high-dimensionality, which collectively obscure subtle biological variations and rare cellular subtypes. This paper investigates the design, system architecture, and deployment dynamics of self-supervised deep learning frameworks engineered to overcome these computational bottlenecks without relying on manual, error-prone cellular annotations. By leveraging advanced contrastive learning, masked autoencoders, and generative adversarial frameworks, self-supervised systems construct robust latent representations that preserve complex, non-linear cellular topologies. This comprehensive analysis evaluates the structural trade-offs between disparate network architectures, prioritizing computational efficiency, spatial scalability, and historical database integration. Beyond raw algorithmic performance, we inspect the systemic infrastructure required to deploy these deep learning models within real-world clinical and translational pipelines. This includes a thorough investigation into algorithmic fairness, demographic representation across diverse patient cohorts, and the socio-technical governance models needed to guarantee data privacy and regulatory compliance. Ultimately, this work offers a unified architectural blueprint for resilient, scalable, and equitable self-supervised deep learning infrastructures in single-cell transcriptomics, providing a roadmap for future interdisciplinary development at the intersection of artificial intelligence, high-throughput biotechnology, and public health policy.